An investigation of pedestrian traffic flow in a representative commercial area in China. Issue 3 (3rd July 2018) - Li, Jianfeng
Abstract: The large number of people that can congregate in urban commercial areas poses a potential risk for pedestrian safety and is an important safety issue for urban administrators. This research describes our investigation of a crowded commercial area to reveal pedestrian traffic flow by counting pedestrians in all transportation nodes over a 14-h period. Some interesting findings were revealed from the on-site investigations: (i) the counting of pedestrian numbers via traffic flow is not exact because the destinations of pedestrians are not fixed, and attention should be paid to the key roads between subway exits and commercial areas; (ii) the proportion of the number of pedestrians between different bus stations is stable because bus numbers at every station are not variable and (iii) the proportion of the number of pedestrians between different subway exits is unstable because subway exits are linked and pedestrians from one station can leave via another exit. These findings serve to assist administrators in on-site crowd control and riot control. Highlights: The proportion of the number of people between different bus stations is stable. The proportion of the number of people between different subway exits is unstable. Counting pedestrian numbers via transportation modes is not exact.